Effect of Different Warm Dense-sparse Waves on Cartilage Pathological Changes of Knee Osteoarthritis - Munan LIN; Xihai LI; Yanhong LIN; Yeqing LIN; Qinghong LIU; Jie GAO; Dehua ZENG; Dongzhong KE (康复学报)
Objective:The influence of warm dense-sparse waves of different wave band on articular cartilage tissue pathological changes in knee osteoarthritis of rats were observed to explore the therapeutic effect of optimal band.Methods:Sixty SD rats were randomly divided into six groups, each group received corresponding intervention method, and the pathological changes of articular cartilage were observed after eight weeks.Results:The pathological changes of articular cartilage were normal in normal group after eight weeks. In model group, articular cartilage surface was rough and the migration layer was exposed, and the nucleus of the cartilage was pyknotic and necrotic. The dense-sparse waves 1∶2 model group showed mild atrophy in cytoplasm, endoplasmic reticulum and mitochondria appeared slightly swollen. The pathological changes of cartilage cell morphology and cell organelles in microwave control group, the dense-sparse waves 1∶1 mode group, and the dense-sparse waves 2∶1 pattern group were better than that in the model group (P<0.01), but worse than that in the dense-sparse waves 1∶2 model group (P<0.05).Conclusion:Warm dense-sparse waves of different wave band can delay the degeneration of knee osteoarthritis chondrocytes and cartilage matrix, and the dense-sparse waves 1∶2 pattern has more obvious effect.